Revolutionizing Industrial Sustainability: Harnessing the Potential of Plastic Waste Recycling - goyal, Sarit (Journal of Advanced Research in Glass, Leather and Plastic Technology; Vol 6 No 1 (2023): Journal of Advanced Research in Glass, Leather and Plastic Technology, 2023)
Despite making a significant contribution to the worldwide problem of plastic pollution, high-income countries are driving up plastic usage. Due to poor management, such as when they are ingested by fish and damaging to human health (cancer is a major disease), the enormous amounts of plastic garbage pose a serious threat to the ecosystem and its inhabitants. In order to increase environmental sustainability, a treatment for plastic trash was examined in this review paper. Since it can replace all solid components, it has been discovered that using recycled plastic waste as a component is the most advantageous.